(untitled) (Signifiances (Signifying), 2019)
Within the scope of a phenomenological and semiotic approach of the language activity, this study focuses on the description of the semiotization of the psychic flux. Furthermore the stress is placed on the several types of semiosis that follow from the different levels of the linguistic analysis (system/norm/speech) : significance, signification, designation, expression.